Water electrolysis anode catalyst layer, preparation method thereof and water electrolysis catalyst coating film
By using a combination of supported catalyst and ionomer in the water electrolytic anode catalytic layer, the problem of slow oxygen precipitation reaction of the anode catalytic layer is solved, the conductivity and catalytic activity are improved, and the catalyst usage is reduced, thus realizing the resource Efficient use.
Patent Information
- Application Number
- CN202411954990.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-02-18
AI Technical Summary
In the proton exchange membrane water electrolytic cell, the kinetics of the oxygen precipitation reaction of the anode catalytic layer are slow and the overpotential is high, resulting in low efficiency of use of iridium-based metal catalysts and large resource consumption.
By using a combination of a supported catalyst and an ionomer in the water electrolytic anode catalytic layer, a structurally stable catalytic layer is formed. The supported catalyst includes a first supported catalyst and a second supported catalyst, which has a higher catalyst loading and conductivity, while the second supported catalyst provides more active sites.
The conductivity of the water electrolytic anode catalytic layer is improved, and the amount of catalyst is reduced and the cost is reduced without affecting the catalytic activity.
Smart Images

Figure CN119465282A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of water electrolysis, and in particular to a water electrolysis anode catalyst layer and a preparation method thereof, and a water electrolysis catalyst coating membrane. Background Art
[0002] Electrochemical water splitting using renewable energy sources such as wind, solar, and geothermal energy is an upcoming green hydrogen production technology. Compared with traditional alkaline electrolyzers, proton exchange membrane (PEM) water electrolyzers have the advantages of fast response speed, high power density, high efficiency, and high gas purity, and are considered to be the next generation of hydrogen production technology. Water electrolysis mainly involves two half-reaction processes, the hydrogen evolution reaction (HER) at the cathode and the oxygen evolution reaction (OER) at the anode. The slower kinetics of the oxygen evolution reaction at the anode and the higher overpotential make the research and development of oxygen evolution catalysts an important direction for the large-scale promotion and application of PEM water electrolysis technology.
[0003] In a proton exchange membrane (PEM) electrolyzer, the catalyst coated membrane (CCM) is the core component of the PEM electrolyzer for producing hydrogen by electrolyzing water. The catalyst coated membrane consists of a proton exchange membrane located in the middle, and a cathode catalyst layer and an anode catalyst layer located on both sides of the proton exchange membrane and in close contact with the proton exchange membrane. When the PEM electrolyzer is working, water generates oxygen under the action of the catalyst in the anode catalyst layer, and generates hydrogen under the action of the catalyst in the cathode catalyst layer.
[0004] However, the catalyst in the anode catalyst layer is widely used iridium-based metal catalyst, which is expensive and has limited resources. Therefore, it is of great significance to optimize the structure of the anode catalyst layer, improve the utilization rate of the catalyst, and reduce the loading amount of the iridium-based metal catalyst without affecting the performance of the electrolyzer. Summary of the invention
[0005] The present application provides a water electrolysis anode catalyst layer and a preparation method thereof, and a water electrolysis catalyst coating membrane, which can improve the conductivity of the water electrolysis anode catalyst layer and reduce the amount of catalyst without affecting the catalytic activity of the water electrolysis anode catalyst layer.
[0006] The embodiment of the present application is implemented as follows:
[0007] In a first aspect, the present application provides an example of a water electrolysis anode catalyst layer, which includes a loaded catalyst and an ionomer, the loaded catalyst includes a first loaded catalyst and a second loaded catalyst, the size of the first loaded catalyst is larger than the size of the second loaded catalyst, the catalyst loading of the first loaded catalyst is larger than the catalyst loading of the second loaded catalyst, and the mass proportion of the first loaded catalyst in the loaded catalyst is not greater than the mass proportion of the second loaded catalyst in the loaded catalyst.
[0008] In the above technical scheme, the water electrolysis anode catalyst layer of the present application is formed by matching a loaded catalyst and an ionomer to form a catalytic layer, wherein the loaded catalyst includes a first loaded catalyst and a second loaded catalyst, and the ionomer can be used as a binder to bond the first loaded catalyst and the second loaded catalyst together to form a catalytic layer with a stable structure, and the ionomer can be used to provide a proton-conducting path to realize the conduction of protons; the first loaded catalyst is loaded with more catalysts than the second loaded catalyst, so that the first loaded catalyst has a relatively high conductivity, and the second loaded catalyst is compared with the first loaded catalyst in the loaded catalyst. The mass ratio, which enables the second loaded catalyst to provide more active sites, and the first loaded catalyst has a larger size than the second loaded catalyst, and the first loaded catalyst can connect the agglomerates of the smaller second loaded catalyst in the water electrolysis anode catalyst layer to form a conductive channel, thereby improving the conductivity of the water electrolysis anode catalyst layer. In addition, the use of the first loaded catalyst and the second loaded catalyst can also reduce the amount of catalyst without affecting the catalytic activity of the water electrolysis anode catalyst layer.
[0009] In some possible embodiments, the catalyst loading of the first supported catalyst is 60% to 80%, and / or the catalyst loading of the second supported catalyst is 30% to 50%.
[0010] In the above technical scheme, the present application makes the catalyst loading of the first loaded catalyst greater than the catalyst loading of the second loaded catalyst by making the catalyst loading of the first loaded catalyst and / or the catalyst loading of the second loaded catalyst within the above range, so that the first loaded catalyst has a relatively high conductivity.
[0011] In some possible embodiments, the first supported catalyst accounts for 30% to 50% by mass of the supported catalyst, and / or the second supported catalyst accounts for 50% to 70% by mass of the supported catalyst.
[0012] In the above technical scheme, the present application makes the mass proportion of the first supported catalyst in the supported catalyst not greater than the mass proportion of the second supported catalyst in the supported catalyst by making the mass proportion of the first supported catalyst in the supported catalyst and / or the mass proportion of the second supported catalyst in the supported catalyst within the above range, and the second supported catalyst can provide more active sites.
[0013] In some possible embodiments, the catalyst supported on the support of the first supported catalyst is at least partially coated on the outer surface of the support of the first supported catalyst;
[0014] Optionally, the carrier of the first supported catalyst includes any one or more of titanium oxide, niobium oxide, tungsten oxide and tantalum oxide;
[0015] Optionally, the catalyst supported on the support of the first supported catalyst includes any one or more of iridium oxide, ruthenium oxide and iridium ruthenium oxide.
[0016] In some possible embodiments, the first supported catalyst is in the shape of a sheet or a rod, and the length of the support of the first supported catalyst is 0.2 μm to 1 μm.
[0017] In the above technical scheme, the present application controls the shape of the first loaded catalyst to be sheet-like or rod-like and the length of the carrier of the first loaded catalyst to be within the above range, which is beneficial for the first loaded catalyst to connect the agglomerates of the smaller second loaded catalyst in the water electrolysis anode catalyst layer to form a conductive channel, thereby improving the conductivity of the water electrolysis anode catalyst layer.
[0018] In some possible embodiments, the catalyst supported on the support of the second supported catalyst is at least partially distributed in a dotted manner on the outer surface of the support of the second supported catalyst;
[0019] Optionally, the carrier of the second supported catalyst includes any one or more of titanium oxide, niobium oxide, tungsten oxide and tantalum oxide;
[0020] Optionally, the catalyst supported on the support of the second supported catalyst includes any one or more of iridium oxide, ruthenium oxide and iridium ruthenium oxide.
[0021] In the above technical solution, the present application enables the second supported catalyst to provide more active sites by distributing the catalyst at least partially in point form on the outer surface of the carrier of the second supported catalyst, thereby improving the catalytic activity of the anode catalyst layer of water electrolysis.
[0022] In some possible embodiments, the second supported catalyst is spherical in shape, and the specific surface area of the carrier of the second supported catalyst is 100 m 2 / g~200m 2 / g.
[0023] In some possible embodiments, at least a portion of the ionomer is coated on the surface of the supported catalyst, and the ionomer includes any one or more of a perfluorosulfonic acid resin, a polyether-based resin, a polyimide-based resin, and a polystyrene sulfonic acid resin.
[0024] In a second aspect, the present application provides a method for preparing a water electrolysis anode catalyst layer, which comprises: applying a catalyst layer slurry comprising a supported catalyst, an ionomer and a solvent to form a water electrolysis anode catalyst layer.
[0025] Among them, the loaded catalyst includes a first loaded catalyst and a second loaded catalyst, the catalyst loading of the first loaded catalyst is greater than the catalyst loading of the second loaded catalyst, and the mass proportion of the first loaded catalyst in the loaded catalyst is not greater than the mass proportion of the second loaded catalyst in the loaded catalyst.
[0026] In the above technical scheme, the preparation method of the water electrolysis anode catalyst layer of the present application is simple, and the obtained water electrolysis anode catalyst layer has a stable structure. It forms a catalyst layer by matching a loaded catalyst and an ionomer, wherein the loaded catalyst includes a first loaded catalyst and a second loaded catalyst, and the ionomer can be used as a binder to bond the first loaded catalyst and the second loaded catalyst together to form a catalyst layer with a stable structure, and the ionomer can be used to provide a proton-conducting path to realize the conduction of protons; the first loaded catalyst is loaded with more catalysts than the second loaded catalyst, so that the first loaded catalyst has a relatively high conductivity, and the second loaded catalyst is compared with the mass proportion of the first loaded catalyst in the loaded catalyst, which enables the second loaded catalyst to provide more active sites, and the first loaded catalyst has a larger size than the second loaded catalyst, and the first loaded catalyst can connect the agglomerates of the smaller second loaded catalyst in the water electrolysis anode catalyst layer to form a conductive channel, thereby improving the conductivity of the water electrolysis anode catalyst layer. In addition, the use of the first loaded catalyst and the second loaded catalyst can also reduce the amount of catalyst without affecting the catalytic activity of the water electrolysis anode catalyst layer.
[0027] In a third aspect, the present application provides a water electrolysis catalyst coating membrane, which includes the water electrolysis anode catalyst layer in the above embodiment or the water electrolysis anode catalyst layer prepared according to the preparation method of the water electrolysis anode catalyst layer in the above embodiment. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.
[0029] Figure 1 A schematic diagram of the structure of a CCM (cathode catalyst layer not shown) according to an embodiment of the present application;
[0030] Figure 2 The polarization curves of Examples 1 to 5 and Comparative Examples 1 to 4 of the present application are shown in FIG.
[0031] Icons: 10 - water electrolysis catalyst coated membrane (CCM); 100 - proton exchange membrane; 200 - water electrolysis anode catalyst layer; 210 - ionomer; 220 - first supported catalyst; 230 - second supported catalyst. DETAILED DESCRIPTION
[0032] The embodiments of the present application will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. In the examples, if specific conditions are not specified, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0033] The following is a specific description of a water electrolysis anode catalyst layer and a preparation method thereof, and a water electrolysis catalyst coating membrane according to an embodiment of the present application:
[0034] See also Figure 1 The present application provides a water electrolysis catalyst coating membrane (CCM) 10, which includes a proton exchange membrane 100 and a water electrolysis anode catalyst layer 200.
[0035] The proton exchange membrane 100 includes a perfluorosulfonic acid proton exchange membrane.
[0036] The water electrolysis anode catalyst layer 200 includes a supported catalyst and an ionomer 210 , wherein the supported catalyst includes a first supported catalyst 220 and a second supported catalyst 230 .
[0037] The size of the first supported catalyst 220 is greater than that of the second supported catalyst 230 .
[0038] It should be noted that the size of the first supported catalyst 220 is greater than the size of the second supported catalyst 230, which means that the length of the first supported catalyst 220 is greater than the length of the second supported catalyst 230. When the second supported catalyst 230 is spherical, the length of the first supported catalyst 220 is greater than the diameter of the second supported catalyst 230; when the second supported catalyst 230 is irregular, the length of the first supported catalyst 220 is greater than the maximum outer diameter of the second supported catalyst 230.
[0039] Optionally, the first supported catalyst 220 is in the shape of a sheet or a rod, and the length of the carrier of the first supported catalyst 220 is 0.2 μm to 1 μm.
[0040] As an example, the length of the support of the first supported catalyst 220 may be 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, or 1 μm.
[0041] The present application controls the shape of the first loaded catalyst 220 to be sheet-like or rod-like and the length of the carrier of the first loaded catalyst 220 to be within the above range, which is beneficial for the first loaded catalyst 220 to connect the agglomerates of the smaller second loaded catalyst 230 in the water electrolysis anode catalyst layer 200 to form a conductive channel, thereby improving the conductivity of the water electrolysis anode catalyst layer 200.
[0042] Optionally, the second supported catalyst 230 is spherical in shape, and the specific surface area of the carrier of the second supported catalyst 230 is 100 m 2 / g~200m 2 / g, the specific surface area of the carrier of the first supported catalyst 220 is smaller than the specific surface area of the carrier of the second supported catalyst 230.
[0043] As an example, the specific surface area of the carrier of the second supported catalyst 230 is 100 m 2 / g, 110m 2 / g, 120m 2 / g, 130m 2 / g, 140m 2 / g, 150m 2 / g, 160m 2 / g, 170m 2 / g, 180m 2 / g, 190m 2 / g or 200m 2 / g.
[0044] Optionally, the particle size of the carrier of the second supported catalyst 230 is 5 nm to 10 nm.
[0045] The catalyst loading amount of the first supported catalyst 220 is greater than the catalyst loading amount of the second supported catalyst 230 .
[0046] Optionally, the catalyst loading amount of the first supported catalyst 220 is 60% to 80%, and / or the catalyst loading amount of the second supported catalyst 230 is 30% to 50%.
[0047] It should be noted that the catalyst loading amount of the first loaded catalyst 220 refers to the mass percentage of the catalyst mass loaded on the carrier of the first loaded catalyst 220 to the total mass of the first loaded catalyst 220, and the catalyst loading amount of the second loaded catalyst 230 refers to the mass percentage of the catalyst mass loaded on the carrier of the second loaded catalyst 230 to the total mass of the second loaded catalyst 230.
[0048] As an example, the catalyst loading of the first supported catalyst 220 may be 60%, 65%, 70%, 75%, or 80%, and / or the catalyst loading of the second supported catalyst 230 may be 30%, 35%, 40%, 45%, or 50%.
[0049] The present application enables the catalyst loading of the first supported catalyst 220 to be greater than the catalyst loading of the second supported catalyst 230 by making the catalyst loading of the first supported catalyst 220 and / or the catalyst loading of the second supported catalyst 230 within the above range, so that the first supported catalyst 220 has a relatively high conductivity.
[0050] Optionally, the catalyst supported on the carrier of the first supported catalyst 220 is at least partially coated on the outer surface of the carrier of the first supported catalyst 220 .
[0051] Optionally, the catalyst supported on the carrier of the first supported catalyst 220 at least partially and completely covers the outer surface of the carrier of the first supported catalyst 220 .
[0052] Optionally, at least part of the catalyst supported on the carrier of the second supported catalyst 230 is distributed in a dotted manner on the outer surface of the carrier of the second supported catalyst 230 .
[0053] The present application enables the second supported catalyst 230 to provide more active sites by distributing the catalyst at least partially in a dotted manner on the outer surface of the carrier of the second supported catalyst 230 , thereby improving the catalytic activity of the water electrolysis anode catalyst layer 200 .
[0054] The mass proportion of the first supported catalyst 220 in the supported catalyst is not greater than the mass proportion of the second supported catalyst 230 in the supported catalyst.
[0055] Optionally, the mass proportion of the first supported catalyst 220 in the supported catalyst is 30% to 50%, and / or the mass proportion of the second supported catalyst 230 in the supported catalyst is 50% to 70%.
[0056] As an example, the mass proportion of the first loaded catalyst 220 in the loaded catalyst can be 30%, 32%, 35%, 38%, 40%, 42%, 45% or 50%, and / or, the mass proportion of the second loaded catalyst 230 in the loaded catalyst can be 50%, 55%, 58%, 60%, 62%, 65%, 68% or 70%.
[0057] The present application enables the mass proportion of the first loaded catalyst 220 in the loaded catalyst to be no greater than the mass proportion of the second loaded catalyst 230 in the loaded catalyst by ensuring that the mass proportion of the first loaded catalyst 220 in the loaded catalyst and / or the mass proportion of the second loaded catalyst 230 in the loaded catalyst are within the above-mentioned range, and the second loaded catalyst 230 can provide more active sites.
[0058] Optionally, the support of the first supported catalyst includes any one or more of titanium oxide, niobium oxide, tungsten oxide and tantalum oxide.
[0059] Optionally, the catalyst supported on the support of the first supported catalyst includes any one or more of iridium oxide, ruthenium oxide and iridium ruthenium oxide.
[0060] Optionally, the support of the second supported catalyst includes any one or more of titanium oxide, niobium oxide, tungsten oxide and tantalum oxide.
[0061] Optionally, the catalyst supported on the support of the second supported catalyst includes any one or more of iridium oxide, ruthenium oxide and iridium ruthenium oxide.
[0062] The mass ratio of the ionomer 210 to the supported catalyst is 0.1 to 0.3:1.
[0063] At least a portion of the ionomer 210 is coated on the surface of the supported catalyst, and the ionomer 210 includes any one or more of perfluorosulfonic acid resin, polyether-based resin, polyimide-based resin and polystyrene sulfonic acid resin.
[0064] The water electrolysis anode catalyst layer 200 of the present application is formed by matching a supported catalyst and an ionomer 210 to form a catalyst layer, wherein the supported catalyst includes a first supported catalyst 220 and a second supported catalyst 230, and the ionomer 210 can be used as a binder to bond the first supported catalyst 220 and the second supported catalyst 230 together to form a catalyst layer with a stable structure, and the ionomer 210 can be used to provide a proton conduction path to conduct protons; the first supported catalyst 220 carries more catalyst than the second supported catalyst 230, so that the first supported catalyst 220 is more stable than the second supported catalyst 230. The supported catalyst 220 has a relatively high conductivity, and the mass proportion of the second supported catalyst 230 in the supported catalyst is greater than that of the first supported catalyst 220, which enables the second supported catalyst 230 to provide more active sites, and the first supported catalyst 220 has a larger size than the second supported catalyst 230, and the first supported catalyst 220 can connect the agglomerates of the smaller-sized second supported catalyst 230 in the water electrolysis anode catalyst layer 200 to form a conductive channel, thereby improving the conductivity of the water electrolysis anode catalyst layer 200. In addition, the combination of the first supported catalyst 220 and the second supported catalyst 230 can also reduce the amount of catalyst without affecting the catalytic activity of the water electrolysis anode catalyst layer 200.
[0065] The present application also provides a method for preparing a water electrolysis anode catalyst layer, which specifically comprises the following steps:
[0066] S1. Preparation of catalytic layer slurry
[0067] The solvent, the ionomer, the first supported catalyst and the second supported catalyst are mixed to prepare a catalyst layer slurry with a solid content of 10% to 20%.
[0068] The solvent includes isopropanol and water, and the volume ratio of isopropanol to water in the solvent is 5:2.
[0069] S2. Preparation of anode catalyst layer for water electrolysis
[0070] The prepared catalyst layer slurry is coated on the surface of the base layer by spraying to form a catalyst layer.
[0071] Optionally, the base layer may be a proton exchange membrane or a polytetrafluoroethylene transfer membrane.
[0072] The preparation method of the water electrolysis anode catalyst layer of the present application is simple, and the prepared water electrolysis anode catalyst layer has a stable structure and high conductivity, and can reduce the amount of catalyst without affecting the catalytic activity.
[0073] The present application also provides a water electrolysis catalyst coating membrane, which includes the water electrolysis anode catalyst layer in the above embodiment or the water electrolysis anode catalyst layer prepared according to the preparation method of the water electrolysis anode catalyst layer in the above embodiment.
[0074] The following is a further detailed description of a water electrolysis anode catalyst layer and a preparation method thereof, and a water electrolysis catalyst coating membrane of the present application in conjunction with embodiments.
[0075] Example 1
[0076] The present invention provides a water electrolysis CCM and a preparation method thereof, which comprises the following steps:
[0077] S1. Preparation of catalytic layer slurry
[0078] The solvent, the ionomer, the first supported catalyst and the second supported catalyst were mixed to prepare a catalyst layer slurry with a solid content of 15%.
[0079] The solvent is a mixture of isopropanol and water, and the volume ratio of isopropanol to water in the solvent is 5:2; the ionomer is a perfluorosulfonic acid resin dispersion D2020, the first loaded catalyst is IrO2 loaded on rod-shaped TiO2, and the second loaded catalyst is IrO2 loaded on granular TiO2.
[0080] The mass ratio of the ionomer to the supported catalyst is 0.2:1; the length of the support of the first supported catalyst is 0.5 μm, the catalyst particles supported on the support of the first supported catalyst are at least partially and completely coated on the outer surface of the support of the first supported catalyst, and the specific surface area of the support of the second supported catalyst is 150 m 2 / g, the particle size of the carrier of the second loaded catalyst is 7nm, and the catalyst particles loaded on the carrier of the second loaded catalyst are at least partially distributed in a point shape on the outer surface of the carrier of the second loaded catalyst; the catalyst loading amount of the first loaded catalyst is 70%, and the catalyst loading amount of the second loaded catalyst is 40%; the mass proportion of the first loaded catalyst in the loaded catalyst is 40%, and the mass proportion of the second loaded catalyst in the loaded catalyst is 60%.
[0081] S2. Preparation of anode catalyst layer for water electrolysis
[0082] The prepared catalyst layer slurry is coated on the surface of the polytetrafluoroethylene membrane (transfer membrane) by spraying to form a water electrolysis anode catalyst layer.
[0083] S3. Preparation of CCM
[0084] The prepared water electrolysis anode catalyst layer coated on the surface of the polytetrafluoroethylene membrane and the cathode Pt / C catalyst layer coated on the polytetrafluoroethylene membrane (transfer membrane) were transferred to the Nafion115 proton exchange membrane by thermal transfer to form a CCM.
[0085] Example 2
[0086] The present invention provides a water electrolysis CCM and a preparation method thereof, which comprises the following steps:
[0087] S1. Preparation of catalytic layer slurry
[0088] The solvent, the ionomer, the first supported catalyst and the second supported catalyst were mixed to prepare a catalyst layer slurry with a solid content of 15%.
[0089] The solvent is a mixture of isopropanol and water, and the volume ratio of isopropanol to water in the solvent is 5:2; the ionomer is a perfluorosulfonic acid resin dispersion D2020, the first loaded catalyst is IrO2 loaded on rod-shaped TiO2, and the second loaded catalyst is IrO2 loaded on granular TiO2.
[0090] The mass ratio of the ionomer to the supported catalyst is 0.2:1; the length of the support of the first supported catalyst is 0.5 μm, the catalyst particles supported on the support of the first supported catalyst are at least partially and completely coated on the outer surface of the support of the first supported catalyst, and the specific surface area of the support of the second supported catalyst is 150 m 2 / g, the particle size of the carrier of the second loaded catalyst is 7nm, and the catalyst particles loaded on the carrier of the second loaded catalyst are at least partially distributed in a point shape on the outer surface of the second loaded catalyst; the catalyst loading amount of the first loaded catalyst is 60%, and the catalyst loading amount of the second loaded catalyst is 50%; the mass proportion of the first loaded catalyst in the loaded catalyst is 40%, and the mass proportion of the second loaded catalyst in the loaded catalyst is 60%.
[0091] S2. Preparation of anode catalyst layer for water electrolysis
[0092] The prepared catalyst layer slurry is coated on the surface of the polytetrafluoroethylene membrane (transfer membrane) by spraying to form a water electrolysis anode catalyst layer.
[0093] S3. Preparation of CCM
[0094] The prepared water electrolysis anode catalyst layer coated on the surface of the polytetrafluoroethylene membrane and the cathode Pt / C catalyst layer coated on the polytetrafluoroethylene membrane were transferred to the Nafion115 proton exchange membrane by thermal transfer to form a CCM.
[0095] Example 3
[0096] The present invention provides a water electrolysis CCM and a preparation method thereof, which comprises the following steps:
[0097] S1. Preparation of catalytic layer slurry
[0098] The solvent, the ionomer, the first supported catalyst and the second supported catalyst were mixed to prepare a catalyst layer slurry with a solid content of 15%.
[0099] The solvent is a mixture of isopropanol and water, and the volume ratio of isopropanol to water in the solvent is 5:2; the ionomer is a perfluorosulfonic acid resin dispersion D2020, the first loaded catalyst is IrO2 loaded on rod-shaped TiO2, and the second loaded catalyst is IrO2 loaded on granular TiO2.
[0100] The mass ratio of the ionomer to the supported catalyst is 0.2:1; the length of the support of the first supported catalyst is 0.5 μm, the catalyst particles supported on the support of the first supported catalyst are at least partially and completely coated on the outer surface of the support of the first supported catalyst, and the specific surface area of the support of the second supported catalyst is 150 m 2 / g, the particle size of the carrier of the second loaded catalyst is 7nm, and the catalyst particles loaded on the carrier of the second loaded catalyst are at least partially distributed in a point shape on the outer surface of the carrier of the second loaded catalyst; the catalyst loading amount of the first loaded catalyst is 80%, and the catalyst loading amount of the second loaded catalyst is 30%; the mass proportion of the first loaded catalyst in the loaded catalyst is 40%, and the mass proportion of the second loaded catalyst in the loaded catalyst is 60%.
[0101] S2. Preparation of anode catalyst layer for water electrolysis
[0102] The prepared catalyst layer slurry is coated on the surface of the polytetrafluoroethylene membrane (transfer membrane) by spraying to form a water electrolysis anode catalyst layer.
[0103] S3. Preparation of CCM
[0104] The prepared water electrolysis anode catalyst layer coated on the surface of the polytetrafluoroethylene membrane and the cathode Pt / C catalyst layer coated on the polytetrafluoroethylene membrane were transferred to the Nafion115 proton exchange membrane by thermal transfer to form a CCM.
[0105] Example 4
[0106] The present invention provides a water electrolysis CCM and a preparation method thereof, which comprises the following steps:
[0107] S1. Preparation of catalytic layer slurry
[0108] The solvent, the ionomer, the first supported catalyst and the second supported catalyst were mixed to prepare a catalyst layer slurry with a solid content of 15%.
[0109] The solvent is a mixture of isopropanol and water, and the volume ratio of isopropanol to water in the solvent is 5:2; the ionomer is a perfluorosulfonic acid resin dispersion D2020, the first loaded catalyst is IrO2 loaded on rod-shaped TiO2, and the second loaded catalyst is IrO2 loaded on granular TiO2.
[0110] The mass ratio of the ionomer to the supported catalyst is 0.2:1; the length of the support of the first supported catalyst is 0.5 μm, the catalyst particles supported on the support of the first supported catalyst are at least partially and completely coated on the outer surface of the support of the first supported catalyst, and the specific surface area of the support of the second supported catalyst is 150 m 2 / g, the particle size of the carrier of the second loaded catalyst is 7nm, and the catalyst particles loaded on the carrier of the second loaded catalyst are at least partially distributed in a dotted manner on the outer surface of the carrier of the second loaded catalyst; the catalyst loading amount of the first loaded catalyst is 70%, and the catalyst loading amount of the second loaded catalyst is 40%; the mass proportion of the first loaded catalyst in the loaded catalyst is 30%, and the mass proportion of the second loaded catalyst in the loaded catalyst is 70%.
[0111] S2. Preparation of anode catalyst layer for water electrolysis
[0112] The prepared catalyst layer slurry is coated on the surface of the polytetrafluoroethylene membrane (transfer membrane) by spraying to form a water electrolysis anode catalyst layer.
[0113] S3. Preparation of CCM
[0114] The prepared water electrolysis anode catalyst layer coated on the surface of the polytetrafluoroethylene membrane and the cathode Pt / C catalyst layer coated on the polytetrafluoroethylene membrane were transferred to the Nafion115 proton exchange membrane by thermal transfer to form a CCM.
[0115] Example 5
[0116] The present invention provides a water electrolysis CCM and a preparation method thereof, which comprises the following steps:
[0117] S1. Preparation of catalytic layer slurry
[0118] The solvent, the ionomer, the first supported catalyst and the second supported catalyst were mixed to prepare a catalyst layer slurry with a solid content of 15%.
[0119] The solvent is a mixture of isopropanol and water, and the volume ratio of isopropanol to water in the solvent is 5:2; the ionomer is a perfluorosulfonic acid resin dispersion D2020, the first loaded catalyst is IrO2 loaded on rod-shaped TiO2, and the second loaded catalyst is IrO2 loaded on granular TiO2.
[0120] The mass ratio of the ionomer to the supported catalyst is 0.2:1; the length of the support of the first supported catalyst is 0.5 μm, the catalyst particles supported on the support of the first supported catalyst are at least partially and completely coated on the outer surface of the support of the first supported catalyst, and the specific surface area of the support of the second supported catalyst is 150 m 2 / g, the particle size of the carrier of the second loaded catalyst is 7nm, and the catalyst particles loaded on the carrier of the second loaded catalyst are at least partially distributed in a point shape on the outer surface of the carrier of the second loaded catalyst; the catalyst loading amount of the first loaded catalyst is 70%, and the catalyst loading amount of the second loaded catalyst is 40%; the mass proportion of the first loaded catalyst in the loaded catalyst is 50%, and the mass proportion of the second loaded catalyst in the loaded catalyst is 50%.
[0121] S2. Preparation of anode catalyst layer for water electrolysis
[0122] The prepared catalyst layer slurry is coated on the surface of the polytetrafluoroethylene membrane (transfer membrane) by spraying to form a water electrolysis anode catalyst layer.
[0123] S3. Preparation of CCM
[0124] The prepared water electrolysis anode catalyst layer coated on the surface of the polytetrafluoroethylene membrane and the cathode Pt / C catalyst layer coated on the polytetrafluoroethylene membrane were transferred to the Nafion115 proton exchange membrane by thermal transfer to form a CCM.
[0125] Comparative Example 1
[0126] The comparative example of the present application provides a water electrolysis CCM and a preparation method thereof, which comprises the following steps:
[0127] S1. Preparation of catalytic layer slurry
[0128] The solvent, the ionomer and the first supported catalyst are mixed to prepare a catalyst layer slurry having a solid content of 15%.
[0129] The solvent is a mixture of isopropanol and water, and the volume ratio of isopropanol to water in the solvent is 5:2; the ionomer is a perfluorosulfonic acid resin dispersion D2020, and the first supported catalyst is IrO2 supported on rod-shaped TiO2.
[0130] The mass ratio of the ionomer to the first loaded catalyst is 0.2:1; the length of the carrier of the first loaded catalyst is 0.5 μm, and the catalyst particles loaded on the carrier of the first loaded catalyst are at least partially and completely coated on the outer surface of the carrier of the first loaded catalyst. The catalyst loading of the first loaded catalyst is 70%, and the total amount of catalyst is the same as that in Example 1.
[0131] S2. Preparation of anode catalyst layer for water electrolysis
[0132] The prepared catalyst layer slurry is coated on the surface of the polytetrafluoroethylene membrane (transfer membrane) by spraying to form a water electrolysis anode catalyst layer.
[0133] S3. Preparation of CCM
[0134] The prepared water electrolysis anode catalyst layer coated on the surface of the polytetrafluoroethylene membrane and the cathode Pt / C catalyst layer coated on the polytetrafluoroethylene membrane were transferred to the Nafion115 proton exchange membrane by thermal transfer to form a CCM.
[0135] Comparative Example 2
[0136] The comparative example of the present application provides a water electrolysis CCM and a preparation method thereof, which comprises the following steps:
[0137] S1. Preparation of catalytic layer slurry
[0138] The solvent, the ionomer and the second supported catalyst were mixed to prepare a catalyst layer slurry with a solid content of 15%.
[0139] The solvent is a mixture of isopropanol and water, and the volume ratio of isopropanol to water in the solvent is 5:2; the ionomer is a perfluorosulfonic acid resin dispersion D2020, and the second supported catalyst is IrO2 supported on granular TiO2.
[0140] The mass ratio of the ionomer to the second supported catalyst is 0.2:1; the specific surface area of the carrier of the second supported catalyst is 150m 2 / g, the particle size of the carrier of the second loaded catalyst is 7nm, the catalyst particles loaded on the carrier of the second loaded catalyst are at least partially distributed in a dotted manner on the outer surface of the carrier of the second loaded catalyst, the catalyst loading amount of the second loaded catalyst is 40%, and the total amount of catalyst is the same as that in Example 1.
[0141] S2. Preparation of anode catalyst layer for water electrolysis
[0142] The prepared catalyst layer slurry is coated on the surface of the polytetrafluoroethylene membrane (transfer membrane) by spraying to form a water electrolysis anode catalyst layer.
[0143] S3. Preparation of CCM
[0144] The prepared water electrolysis anode catalyst layer coated on the surface of the polytetrafluoroethylene membrane and the cathode Pt / C catalyst layer coated on the polytetrafluoroethylene membrane were transferred to the Nafion115 proton exchange membrane by thermal transfer to form a CCM.
[0145] Comparative Example 3
[0146] The comparative example of the present application provides a water electrolysis CCM and a preparation method thereof, which comprises the following steps:
[0147] S1. Preparation of catalytic layer slurry
[0148] The solvent, the ionomer, the first supported catalyst and the second supported catalyst were mixed to prepare a catalyst layer slurry with a solid content of 15%.
[0149] The solvent is a mixture of isopropanol and water, and the volume ratio of isopropanol to water in the solvent is 5:2; the ionomer is a perfluorosulfonic acid resin dispersion D2020, the first loaded catalyst is IrO2 loaded on rod-shaped TiO2, and the second loaded catalyst is IrO2 loaded on granular TiO2.
[0150] The mass ratio of the ionomer to the supported catalyst is 0.2:1; the length of the support of the first supported catalyst is 0.5 μm, the catalyst particles supported on the support of the first supported catalyst are at least partially and completely coated on the outer surface of the support of the first supported catalyst, and the specific surface area of the support of the second supported catalyst is 150 m 2 / g, the particle size of the carrier of the second loaded catalyst is 7nm, and the catalyst particles loaded on the carrier of the second loaded catalyst are at least partially distributed in a dotted manner on the outer surface of the carrier of the second loaded catalyst; the catalyst loading amount of the first loaded catalyst is 40%, and the catalyst loading amount of the second loaded catalyst is 60%; the mass proportion of the first loaded catalyst in the loaded catalyst is 40%, and the mass proportion of the second loaded catalyst in the loaded catalyst is 60%, and the total amount of catalyst is the same as that in Example 1.
[0151] S2. Preparation of anode catalyst layer for water electrolysis
[0152] The prepared catalyst layer slurry is coated on the surface of the polytetrafluoroethylene membrane (transfer membrane) by spraying to form a water electrolysis anode catalyst layer.
[0153] S3. Preparation of CCM
[0154] The prepared water electrolysis anode catalyst layer coated on the surface of the polytetrafluoroethylene membrane and the cathode Pt / C catalyst layer coated on the polytetrafluoroethylene membrane were transferred to the Nafion115 proton exchange membrane by thermal transfer to form a CCM.
[0155] Comparative Example 4
[0156] The comparative example of the present application provides a water electrolysis CCM and a preparation method thereof, which comprises the following steps:
[0157] S1. Preparation of catalytic layer slurry
[0158] The solvent, the ionomer, the first supported catalyst and the second supported catalyst were mixed to prepare a catalyst layer slurry with a solid content of 15%.
[0159] The solvent is a mixture of isopropanol and water, and the volume ratio of isopropanol to water in the solvent is 5:2; the ionomer is a perfluorosulfonic acid resin dispersion D2020, the first loaded catalyst is IrO2 loaded on rod-shaped TiO2, and the second loaded catalyst is IrO2 loaded on granular TiO2.
[0160] The mass ratio of the ionomer to the supported catalyst is 0.2:1; the length of the support of the first supported catalyst is 0.5 μm, the catalyst particles supported on the support of the first supported catalyst are at least partially and completely coated on the outer surface of the support of the first supported catalyst, and the specific surface area of the support of the second supported catalyst is 150 m 2 / g, the particle size of the carrier of the second loaded catalyst is 7nm, and the catalyst particles loaded on the carrier of the second loaded catalyst are at least partially distributed in a point shape on the outer surface of the carrier of the second loaded catalyst; the catalyst loading amount of the first loaded catalyst is 70%, and the catalyst loading amount of the second loaded catalyst is 40%; the mass proportion of the first loaded catalyst in the loaded catalyst is 60%, and the mass proportion of the second loaded catalyst in the loaded catalyst is 40%, and the total amount of catalyst is the same as that in Example 1.
[0161] S2. Preparation of anode catalyst layer for water electrolysis
[0162] The prepared catalyst layer slurry is coated on the surface of the polytetrafluoroethylene membrane (transfer membrane) by spraying to form a water electrolysis anode catalyst layer.
[0163] S3. Preparation of catalyst coating membrane
[0164] The prepared water electrolysis anode catalyst layer coated on the surface of the polytetrafluoroethylene membrane and the cathode Pt / C catalyst layer coated on the polytetrafluoroethylene membrane were transferred to the Nafion115 proton exchange membrane by thermal transfer to form a CCM.
[0165] Test Example 1
[0166] The water electrolysis catalyst coating membranes prepared in Examples 1 to 5 and Comparative Examples 1 to 4 were packaged with titanium felt for the anode and carbon paper GDL for the cathode to form an electrolytic cell. The current was scanned from 0.01 A / cm 2 Up to 4A / cm2 , record the current and voltage values, the polarization curve is as follows Figure 2 The polarization curve analysis values are shown in Tables 1 and 2.
[0167] Table 1 Polarization curves of Examples 1 to 5 and Comparative Examples 1 to 4 with a current density of 1 A / cm 2 and 2A / cm 2 The parsed value of
[0168]
[0169] Table 2 Polarization curves of Examples 1 to 5 and Comparative Examples 1 to 4 with a current density of 3 A / cm 2 and 4A / cm 2 The parsed value of
[0170]
[0171] It can be seen from Examples 1 to 5 that the water electrolysis catalyst coating membrane prepared by the preparation method of the present application has lower ohmic polarization loss and catalyst activity polarization loss in the catalyst membrane electrode performance test, indicating that it has both good activity and conductivity.
[0172] From the comparison between Comparative Example 1 and Example 1, it can be seen that the water electrolysis catalyst coating membrane of Comparative Example 1 only contains the first supported catalyst and no second supported catalyst, and its catalyst activity polarization loss is significantly increased compared with Example 1, indicating its poor activity.
[0173] From the comparison between Comparative Example 2 and Example 1, it can be seen that the water electrolysis catalyst coating membrane of Comparative Example 2 only contains the second supported catalyst and no first supported catalyst, and its ohmic polarization loss is significantly increased compared with Example 1, indicating that its conductivity is poor.
[0174] By comparing Comparative Example 3 and Example 1, it can be seen that the catalyst loading of the first supported catalyst in Comparative Example 3 is less than the catalyst loading of the second supported catalyst, the total amount of catalyst remains unchanged, and its ohmic polarization loss increases compared with Example 1, indicating that its conductivity has deteriorated, and there is no obvious change in the catalyst activity polarization loss, indicating that the activity has not been significantly improved.
[0175] By comparing Comparative Example 4 and Example 1, it can be seen that in Comparative Example 4, the mass proportion of the first supported catalyst in the supported catalyst is greater than the mass proportion of the second supported catalyst in the supported catalyst, the total amount of catalyst remains unchanged, and its catalyst activity polarization loss increases compared with Example 1, indicating that the activity is slightly worse, and the reduction in Ohm plan loss indicates that the conductivity is improved.
[0176] The above description is only a specific embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A water electrolysis anode catalyst layer, characterized in that: The water electrolysis anode catalyst layer includes a loaded catalyst and an ionomer, the loaded catalyst includes a first loaded catalyst and a second loaded catalyst, the size of the first loaded catalyst is larger than the size of the second loaded catalyst, the catalyst loading of the first loaded catalyst is larger than the catalyst loading of the second loaded catalyst, and the mass proportion of the first loaded catalyst in the loaded catalyst is not greater than the mass proportion of the second loaded catalyst in the loaded catalyst.
2. The water electrolysis anode catalyst layer according to claim 1, characterized in that: The catalyst loading of the first supported catalyst is 60% to 80%, and / or; The catalyst loading amount of the second supported catalyst is 30% to 50%.
3. The water electrolysis anode catalyst layer according to claim 1, characterized in that: The mass proportion of the first supported catalyst in the supported catalyst is 30% to 50%, and / or; The mass proportion of the second supported catalyst in the supported catalyst is 50% to 70%.
4. The water electrolysis anode catalyst layer according to claim 1, characterized in that: The catalyst supported on the carrier of the first supported catalyst is at least partially coated on the outer surface of the carrier of the first supported catalyst; Optionally, the carrier of the first supported catalyst includes any one or more of titanium oxide, niobium oxide, tungsten oxide and tantalum oxide; Optionally, the catalyst supported on the carrier of the first supported catalyst includes any one or more of iridium oxide, ruthenium oxide and iridium ruthenium oxide.
5. The water electrolysis anode catalyst layer according to claim 4, characterized in that: The first supported catalyst is in the shape of a sheet or a rod, and the length of the carrier of the first supported catalyst is 0.2 μm to 1 μm.
6. The water electrolysis anode catalyst layer according to claim 1, characterized in that: The catalyst supported on the carrier of the second supported catalyst is at least partially distributed in a dotted manner on the outer surface of the carrier of the second supported catalyst; Optionally, the carrier of the second supported catalyst includes any one or more of titanium oxide, niobium oxide, tungsten oxide and tantalum oxide; Optionally, the catalyst supported on the carrier of the second supported catalyst includes any one or more of iridium oxide, ruthenium oxide and iridium ruthenium oxide.
7. The water electrolysis anode catalyst layer according to claim 6, characterized in that: The second supported catalyst is spherical in shape, and the specific surface area of the carrier of the second supported catalyst is 100 m 2 / g~200m 2 / g.
8. The water electrolysis anode catalyst layer according to claim 1, characterized in that: At least a portion of the ionomer is coated on the surface of the supported catalyst, and the ionomer includes any one or more of perfluorosulfonic acid resin, polyether-based resin, polyimide-based resin and polystyrene sulfonic acid resin.
9. A method for preparing a water electrolysis anode catalyst layer, characterized in that: The method for preparing the water electrolysis anode catalyst layer comprises: coating a catalyst layer slurry comprising a supported catalyst, an ionomer and a solvent to form the water electrolysis anode catalyst layer; Wherein, the loaded catalyst comprises a first loaded catalyst and a second loaded catalyst, the catalyst loading amount of the first loaded catalyst is greater than the catalyst loading amount of the second loaded catalyst, and the mass proportion of the first loaded catalyst in the loaded catalyst is not greater than the mass proportion of the second loaded catalyst in the loaded catalyst.
10. A water electrolysis catalyst coating membrane, characterized in that: The water electrolysis catalyst coating membrane comprises the water electrolysis anode catalyst layer according to any one of claims 1 to 8 or the water electrolysis anode catalyst layer prepared by the method for preparing the water electrolysis anode catalyst layer according to claim 9.